ASSESSMENT OF THE RESULTS OF LAPAROSCOPIC SURGERY FOR ENDOMETRIOSIS IN THE OVARY (Vietnam Journal of Community Medicine, 2022)
Objective: Evaluation of treatment results of endometrioma in the ovary by laparoscopy.Subjects and methods: A retrospective cross-sectional description of 81 patients withendometriosis cysts operated at Nghe An Obstetrics and Pediatrics Hospital.Results: Dysmenorrhea was the main reason for patients to go to the doctor (35.8%);Laparoscopy correctly diagnosed 96.3%; The rate of laparoscopic surgery is 87.7%; The rate ofcyst removal from endometriosis ± de-adhesion is 87.7%; Laparoscopic surgery has a fastersurgery time than the open surgery group (61.2 ± 17.0 minutes versus 82.0 ± 23.8 minutes), p
Keywords: Endometrioma in the ovary, laparoscopy surgery.